Understanding language teacher wellbeing: An ESM study of daily stressors and uplifts. (July 2023) - Gregersen, Tammy; Mercer, Sarah; MacIntyre, Peter; Talbot, Kyle; Banga, Claire Ann
This study focuses on understanding language teachers' lived experiences of their stressors and positive uplifts from a holistic perspective covering their professional lives in school, their personal lives beyond, and the connection between the two. The aim was to explore the nature of teachers' experiences of stress and how they spilled over from work into home domains. We also were keen to understand the dynamics of their experiences of stress and how their perception of daily stressors was related to their overall sense of wellbeing as well as their life and chronic stressors. The data were collected via a specially created app, which collected survey data and experience sampling method (ESM) data from language teachers across the globe. Teachers' wellbeing was investigated using the PERMA Profiler (Butler & Kern, 2016), their personality using Goldberg's (1992) Big Five measurement tool, and a questionnaire on chronic stressors and stressful life events. From a larger sample ( n = 47), a set of 6 case studies of teachers who scored highly for wellbeing and those who scored low on wellbeing was examined to explore in depth and across time, the relationships between overall wellbeing, chronic stressors and stressful life events, the experience of daily stressors, and perceptions of health. The findings point to the complexity of the relationships between stress, wellbeing, and health as well as the dynamism of stress and the relationships between stress experienced in the workplace and at home. The study has important implications for research in this area and reveals the merits of working with this innovative data collection tool.